The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.12911/22998993/150004
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Titanium-Magnesium Production Waste

Abstract: The article presents the results of research on the processing of such wastes of titanium-magnesium production as sludge from sludge dumps and fine dump dusts from the electric smelting of ilmenite concentrates. The results of nitric acid leaching of sludge with the transfer of calcium into solution and the production of calcium nitrate are given. Titanium-containing cake after nitric acid leaching of sludge and electric smelting dust cannot be returned to the technological process due to its high silica conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Silicon fluorides were separated in the form of sublimates at the first stage of processing of fine dust obtained from the electric smelting of ilmenite concentrates; a sample of dust was mixed with ammonium bifluoride in a 1:1 ratio. The process was performed at 260 °C for 6 h [ 35 , 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Silicon fluorides were separated in the form of sublimates at the first stage of processing of fine dust obtained from the electric smelting of ilmenite concentrates; a sample of dust was mixed with ammonium bifluoride in a 1:1 ratio. The process was performed at 260 °C for 6 h [ 35 , 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Dust contains titanium-containing phases: iron titanium oxides (Fe 2 TiO 5 and Fe 1.5 Ti 0.5 O 3 ), magnesium titanium oxide (MgTi 2 O 5 ), and titanium oxide (TiO 2 ) [ 35 ]. The desiliconized residues are mostly represented by such titanium-containing phases as (NH 4 ) 2 TiF 6 , Ti 6 O 11 ; there is also a (NH 4 ) 0.8 TiOF 2.8 phase [ 37 ]. Taking into account the results of XRD analysis of dusts and desiliconized residues of their fluorination, the process of titanium fluoride formation can be represented for the main phases of iron titanium oxides (Fe 2 TiO 5 and Fe 1.5 Ti 0.5 O 3 ), and magnesium titanium oxide (MgTi 2 O 5 ), in dusts, by the following reactions: …”
Section: Resultsmentioning
confidence: 99%
“…XRD analysis showed that formed ammonium hexafluoride does not sublimate completely in 2-4 h. The reaction of ilmenite fluorination is not completed (Figure 5). An increase in the fluorination duration up to 6 h allowed almost complete extraction of silicon in the sublimations (Figure 6) [32]. An increase in the fluorination duration up to 6 h allowed almost complete extraction of silicon in the sublimations (Figure 6) [32].…”
Section: Effect Of the Fluoridation Durationmentioning
confidence: 96%
“…An increase in the fluorination duration up to 6 h allowed almost complete extraction of silicon in the sublimations (Figure 6) [32]. An increase in the fluorination duration up to 6 h allowed almost complete extraction of silicon in the sublimations (Figure 6) [32]. The study of the influence of specific ammonium bifluoride consumption on fluorination of electrical melting components of ilmenite concentrate dust with formation and sublimation of silicon fluoride was performed at a temperature of 260 °С with a 6 h…”
Section: Effect Of the Fluoridation Durationmentioning
confidence: 99%
“…Scandium extraction is carried out with a 70% solution of tributyl phosphate in kerosene; the resulting scandium-enriched organic phase is washed from impurities with strong hydrochloric acid (220-240 g/l HCl); then the scandium extract is transferred to the aqueous phase (reextract) with a 7% hydrochloric acid solution. From the reextraction of oxalic acid, oxalates of scandium and other metals are precipitated, the resulting pulp is filtered, a solid precipitate of oxalates is dried and heated at 700ºc and a technical oxide containing 40-60% Sc2O3 is obtained [ [24], [25]].…”
Section: Sc2o3+6cl2+3c=4sccl3+3co2mentioning
confidence: 99%